Development of a Plum (Japanese Apricot) Seed Crusher to Control Harmful Larvae (Eurytoma maslovskii) in Plum Orchard - Ali, Mohammod; Kim, Bok Seok; Park, Seong-Jin; Kim, Hyuck-Joo (Journal of Agriculture & Life Science, 2019)
The Eurytoma maslovskii conduces the unexpected plum dropping. It stayed overwinter inside the pits of the dropped plums and able to oviposit on plum surface when the diameter of the plums are over 16 mm prior to endocarp hardening. To control this harmful pests is too much essential to plum orchard. Therefore, the plum seed crusher (PSC) was designed and developed according to the purpose of perishing the pests through destroying the dropped plums. The rocks and the weeds were removed from the plum orchard prior to the test. Manually operated plum seed crusher picked-up the dropped plums from the ground and crushed them. The performance of PSC was evaluated by applying 2.5 and 3.0 km/h travelling speeds, and controlling the gaps; 18, and 28 mm intervals between plum pick-up discs. The test result showed the plum pick-up rate was 98±2.0%, and 92±5.3% with the machine travelling speed of 3.0 km/h in laboratory. Further, it changed to 95±8.7%, and 93±5.8% when the travelling speed was used 2.5 km/h. In both cases of test plum pick-up discs were maintained 18 mm, and 28 mm gap intervals, respectively. Furthermore, in field conditions, pursuing to similar gap intervals, the plum pick-up rate was 94±4.0%, and 92±2.0% with the speed of 3.0 km/h albeit it showed 92±4.0%, and 90±3.5% when the speed was decreased to 2.5 km/h. The maximum plum pick-up rate was found at 18 mm disc intervals with 3.0 km/h travelling speeds. The crushing teeth were selected 8 mm in height by repeated test to destroy the plum seeds. The result showed 100% crushing efficiency was facilitated to entire tests at 280 RPM crushing speeds regardless of plum sizes and shapes. This machine is preferred for the farmers to control the damage of plums by preventing the propagation of the identified pests.